Adult Consequences of Bully Victimization: Are Children or Adolescents More Vulnerable to the Victimization Experience?. (October 2017) - Hoffman, Chrystina Y.; Phillips, Matthew D.; Daigle, Leah E.; Turner, Michael G.
Although evidence exists that bully victimizations are related to a range of negative outcomes later in the life course, existing research has largely ignored the timing of the victimization experience. Using data from the National Longitudinal Survey of Youth 1997, the present study uses propensity score matching to investigate the adult consequences of victims experiencing repeated bullying in childhood, adolescence, or both developmental periods. Individuals victimized as children reported higher instances of arrests, convictions, violence, and substance use than child nonvictims. The results point to the importance of implementing effective prevention programs early in the life course.